Implikasi al-Dakhīl dalam Tafsir: Telaah Kisah Nabi Ayub dalam Al-Kashf wa al-Bayān ‘an Tafsīr al-Qur’ān - Adawy, Abdillah Amiril; Aqil, Zaky Muhammad (Canonia Religia, 2024)
This article examines the presence of al-dakhīl (infiltrations) in the Qur’anic exegesis of al-Thaʿlabī. The term al-dakhīl refers to unauthentic or unverifiable elements that have been incorporated by exegetes into their commentaries. A particularly significant example is its appearance in the interpretation of verses concerning the story of Prophet Ayyub. Various classical tafsīr works depict Ayyub as a prophet blessed with wealth, family, and worldly comfort, who is later subjected to severe trials, including the loss of all possessions and affliction with chronic illness. He is portrayed as enduring these hardships patiently for years, supported by his loyal wife, until God restored his well-being. This study focuses on how al-dakhīl appears in the narration of this story within al-Kashf wa al-Bayān ʿan Tafsīr al-Qurʾān. Employing a library research method, the primary source is al-Thaʿlabī’s tafsīr, supported by secondary sources relevant to the topic. The findings indicate that al-Thaʿlabī was relatively uncritical in incorporating narrative reports, particularly isrāʾīliyyāt (Judeo-Christian traditions), without clear evaluative commentary. These infiltrations often contradict core theological principles, such as the dignity of prophets, and include excessive dramatizations that are deemed inconsistent with prophetic character. This study contributes to tafsīr studies by encouraging scholars to critically assess transmitted reports and avoid relying on unreliable narratives in Qur’anic interpretation, especially within classical exegetical texts.